Exploraciones arqueológicas en la huaca Choque Ispana, valle de Huaura - Ruiz Estrada, Arturo (2006)
The valley of Huaura-Huacho contains valuable arqueological monuments that in the twentieth century began to be explored in depth and with new theoretical and documentary tools. Choque Ispana and Carquin are the substantive sanctuaries of this regional Yunga society that was destroyed at the beginning of seventeenth century by the extirpation of idolatry campaign. After a rapid examination of the existing bibliography, the author presents a meticulous analysis of the variety of existing archaeological materials, followed by a set of ideas on the society and the interrelations between these costal towns and the ones located in the mountain range of Chancay.